Psychosocial Challenges Associated with Caregiving in the Context of Pediatric HIV in Rural Eastern Cape - Lentoor, Antonio G. (Frontiers in Public Health, 2017)
Background: While survival among HIV infected children has increased due to combination Antiretroviral Therapy (cART), many children remain vulnerable to the adverse effects of poverty and family disruptions as a result of the loss of one or both biological parents to Acquired Immunodeficiency Syndrome (AIDS). The aim of this qualitative study was to develop an understanding of the psychosocial challenges experienced by caregivers caring for a child with perinatally acquired HIV. Method: A series of interviews were conducted with 44 HIV positive and negative primary caregivers of HIV + children. Data were analysed through Interpretative phenomenological analysis (IPA) using NVivo8 software. Findings: The findings suggest that caregiving is compromised by inadequate, financial resources and single-headed households where mainly grandparents assume the role of primary caregivers of HIV+ children. HIV remains a stigmatized illness that weakens support networks, as well as timeous and free accessibility to healthcare. This has a negative impact on the mental health of caregivers, with the majority of women in the study displaying symptoms of depression. Conclusion: The findings highlight the contextual challenges of caregiving in the presence of HIV, which impacts negatively on social ecology of the families. The need for interventions to enhance resilience and coping in families confronted with HIV is indicated.